Propuesta de diseño del sistema de alcantarillado sanitario mediante software la Ciudadela Santa Elena – Bucay - Cisneros Martínez, Alan Gabriel (2024)
The project focuses on the design proposal for a sanitary sewerage system in the Santa Elena citadel of Bucay. The first chapter presents the problem, which includes the lack of access to sanitation services globally and in Ecuador, along with the lack of regulations and the discharge of untreated waste into rivers. Objectives are formulated to assess the current state of the sewerage system and propose improvements. Chapter 2 addresses the theoretical and legal framework, which provides the conceptual context and analyzes the laws and regulations pertinent to the design and operation of sewerage systems in Ecuador and specifically in Bucay and the Santa Elena citadel. Chapter 3 defines the approach to the research, which combines qualitative and quantitative techniques. A mixed approach is used to gather information and establish design criteria. Qualitative research focuses on understanding subjective and quantitative reality in the collection and analysis of numerical data. The results reveal that the current sanitary sewer system is not optimally designed, with problems such as excessive pipe diameters. Criteria such as population, area and slopes of the land are used in the design of the health network using digital tools. Visual inspection and surveys complement the information collected. It is concluded that the sewer problems could be solved without the need for a total renovation.